Language barriers during vaccination practice, the point of view of healthcare providers - Bianconi, Alessandro; Zanutto, Giorgia; Castagna, Gisele; Cola, Angela Andrea; De Gioia, Esther Rita; Longo, Giulia; Sicari, Gaia; Tomaiuolo, Giulia; Todeschini, Renato; Pandolfi, Paolo; Gori, Davide (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Background. Language barriers are one of the main obstacles faced by migrants in accessing healthcare services. A compromised communication between migrants and Healthcare Providers in vaccination setting can result in increased vaccine hesitancy and decreased vaccine uptake. The objective of the current study is to investigate Healthcare Providers’ perceptions about linguistic barriers faced during both routinary vaccination practice and the extraordinary vaccination program for Ukrainian refugees in the Local Health Authorities of Bologna and Romagna (Italy).Methods. A cross-sectional study was conducted through the administration of a questionnaire examining Healthcare Providers’ perceptions. A descriptive analysis and a multiple logistic regression model were adopted to analyze the collected data.Results. Language barriers resulted as an obstacle to informed consent and to doctor-patient relationship. The strategies adopted were perceived as helpful in increasing vaccination adherence, despite communication difficulties were still experienced during refugees’ vaccinations. Results suggest that the implementation of translated material and the use of professional interpreters may represent important strategies to overcome linguistic barriers, along with Healthcare Providers’ training. Healthcare Providers’ opinions could assist the implementation of new tools capable of countering language barriers.Conclusions. The current study represents an example of providers’ involvement in understanding the complexities behind the issue of language barriers in vaccination practice.